Community composition and population dynamics of vertebrates in the State National Nature Park “Burabay” - Khussainov, A.T.; Shulembayeva, K.M.; Arkhipov, E.; Fakhrudenova, I.B.; Durmekbayeva, Sh.N. (Fundamental and Experimental Biology, 2022)
The article presents the analysis results of vertebrate community composition in the State National Natural Park “Burabay” and its population dynamics for 2016–2020, as a basic component of the ecological network of specially protected natural areas, ensuring the conservation and restoration of biological diversity, both typical and unique landscapes. The route method of animal registration on the trial plot was applied to study and estimate the number of ungulates, carnivores, rodents, and guans. The animal life forms were classified according to the morphology of A.N. Formazov. The typical nature of the species composition of the park is confirmed by the presence of characteristic communities inherent in the steppe zone. The uniqueness of the species composition of vertebrates lies in the presence of species characteristic to the forest ecosystem; boreal relic animals; species of animals listed in the Red Book of Kazakhstan and species diversity.